Beyond rupture: archaeological insights into resilience, resistance and adaptation in industrializing Aysén Patagonia - Letelier Cosmelli, Javiera; Nuevo-Delaunay, Amalia; Méndez, César; Reyes, Omar (Frontiers in Environmental Archaeology, 2025)
IntroductionThe Aysén region in central-western Patagonia, inhabited for over 12,000 years, presents a valuable case for examining the long-term resilience and adaptation of non-industrial societies to industrial expansion. During the twentieth century, state-driven policies promoted livestock farming, logging, and mining, resulting in profound socioecological transformations that reshaped landscapes and challenged indigenous and rural Creole communities. Rather than an abrupt rupture, industrialization is best understood as part of a longer-term process of environmental and social change.MethodsThis research employs a multiscale approach that integrates archaeological, historical, and environmental data to examine long-term human–environment interactions. Special attention is given to overcoming archaeological selection bias, whereby large industrial sites dominate the record and obscure smaller-scale adaptations critical to local dynamics.ResultsThe analysis reveals that preindustrial strategies of resilience persisted, adapted, and transformed during the industrial expansion of the twentieth century. These findings highlight how indigenous and rural communities navigated industrial pressures while maintaining elements of continuity with earlier lifeways.DiscussionBy tracing these processes across various temporal scales, this study demonstrates how archaeological perspectives can enrich research on global change. Long-term records illuminate resilience, resistance, and sustainability in contexts of industrialization, while also underscoring methodological challenges in identifying such processes in the archaeological record.